Основні характеристики публіцистичного наративу - Шурма, Світлана; Shurma, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті визначено основні змістові, прагматичні та стилістичні риси публіцистичних наративів. Основну увагу зосереджено на понятті наративної стратегії як принципу організації тексту газетної статті. Встановлено такі характеристики наративу, як подієвість, темпоральність, інтенціональність, оцінність та референціальність; з’ясовано роль наративів у формуванні колективної пам’яті. The article deals with the basic content, pragmatic and stylistic features of publisistic narrative. The main attention is paid to the notion of narrative strategy as a defining principle of structuring the text of a newspaper article. The narrative is defined as a text (in a broad sense) or a number of texts which describe socially important events in the sequence of their deployment and which are constructed in accordance with certain language and content models. The elements of newspaper narrative include: 1) eventfulness, 2) events presentation sequence or chain of scenes, 3) temporality, 4) the experience of perception. One more factor which determines the content of the narrative is its referentiality to objects that exist only in the real world. The author argues that the mass media texts in their bulk contribute to the formation of social memory.
Basic Characteristics of the Publicistic Narrative.
Keywords: наратив; наративна стратегія; газетна стаття; подія; narrative; narrative strategy; newspaper article; event